2021
DOI: 10.1002/mabi.202000419
|View full text |Cite
|
Sign up to set email alerts
|

Poly(Vinyl Alcohol)‐Hydrogel Microparticles with Soft Barrier Shell for the Encapsulation of Micrococcus luteus

Abstract: The encapsulation of bacteria in polymers results in hybrid materials that are essential for the long‐term biological activity of bacteria and formulations in practical applications. Here, the problem of bacterial escape and the exchange of metabolism products from hydrogel microparticles within an aqueous environment are addressed. Bacteria are encapsulated in chemically cross‐linked poly(vinyl alcohol) (PVA) hydrogel‐microparticles followed by their encapsulation in a pH‐responsive and soft antibacterial she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…[23] Methods of cell encapsulation have been reviewed; [24] encapsulation was proposed within a wide variety of shells and capsules, based on a materials as diverse as silica, [25] gold, [26] calcium carbonate, [27] metal-organic frameworks, [28] layer-by-layer (LbL) assemblies, [29] calcium phosphate, [30] polydopamine, [31] tannic acid, [32] or (interpenetrated) networks of hydrogels. [33] Since it was shown that stiffer materials generally prevent microbial growth, [24k] we restrict our focus to studies in which bacteria are coated by soft (bio) organic shells, which leads to an already large and non-exhaustive list of bacteria which can be encapsulated while preserving their metabolic activity such as Alcaligenes faecalis, [30b] Allochromatium vinosum, [34] Bacillus (coagulans, [29a] subtilis [29c,d,35] ), Bifidobacterium (adolescentis, [36] breve, [23c,35a] longum [37] ), Enterococcus mundtii, [38] Escherichia coli, [29e,f,33d,35a,39] Gluconacetobacter xylinus, [39b] Lactobacillus (acidophilus, [29b,40] bulgaricus, [41] casei, [42] paracasei, [41b] plantarum, [43] reuteri, [44] rhamnosus, [45] zeae [46] ), Micrococcus luteus, [47] Staphylococcus aureus, [35a] S. epidermidis, [21,48] a variety of probiotics, [33b,49] and cyanobacteria. [50] Encapsulation of bacteria was shown to be able to prolong their storage time for periods as long as 1.5 year.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23] Methods of cell encapsulation have been reviewed; [24] encapsulation was proposed within a wide variety of shells and capsules, based on a materials as diverse as silica, [25] gold, [26] calcium carbonate, [27] metal-organic frameworks, [28] layer-by-layer (LbL) assemblies, [29] calcium phosphate, [30] polydopamine, [31] tannic acid, [32] or (interpenetrated) networks of hydrogels. [33] Since it was shown that stiffer materials generally prevent microbial growth, [24k] we restrict our focus to studies in which bacteria are coated by soft (bio) organic shells, which leads to an already large and non-exhaustive list of bacteria which can be encapsulated while preserving their metabolic activity such as Alcaligenes faecalis, [30b] Allochromatium vinosum, [34] Bacillus (coagulans, [29a] subtilis [29c,d,35] ), Bifidobacterium (adolescentis, [36] breve, [23c,35a] longum [37] ), Enterococcus mundtii, [38] Escherichia coli, [29e,f,33d,35a,39] Gluconacetobacter xylinus, [39b] Lactobacillus (acidophilus, [29b,40] bulgaricus, [41] casei, [42] paracasei, [41b] plantarum, [43] reuteri, [44] rhamnosus, [45] zeae [46] ), Micrococcus luteus, [47] Staphylococcus aureus, [35a] S. epidermidis, [21,48] a variety of probiotics, [33b,49] and cyanobacteria. [50] Encapsulation of bacteria was shown to be able to prolong their storage time for periods as long as 1.5 year.…”
Section: Introductionmentioning
confidence: 99%
“…[50] Encapsulation of bacteria was shown to be able to prolong their storage time for periods as long as 1.5 year. [51] More relevant to our aim are studies showing that bacteria can be kept growing and metabolically-active while being prevented from escaping; for instance, confinement without escaping during 72 h, > 3 days, 7 days, > 20 days and 5 weeks were reported for, respectively, E. coli in an alginate core surrounded by a tough shell made of chemically-crosslinked polyacrylamide and physically-crosslinked alginate, [33d] S. epidermidis in polysulfone microtubes, [48b] B. subtilis in porous micro-needles of poly(ethylene glycol) diacrylate, [35d] and M. luteus in a poly(vinyl alcohol) (PVA) core surrounded by a shell of pH-responsive poly(N,N-diethylamino ethyl methacrylate) [47] or poly(methyl methacrylate). [51] In contrast to the extensively studied probiotics encapsulation for food industry and gastrointestinal therapy, [22b,45,52] the encapsulation of commensal skin bacteria was only considered recently due to a growing interest for bacteriotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the hydroxyl group along the macromolecular chain, it presents a hydrophilic character 13,14 while providing excellent film or fiber‐forming capabilities beside high tensile strength and flexibility 15–17 . Thus, to date a number of PVA‐based blended films have drawn the preoccupation of researchers to develop biomaterials with exceptional combined properties 9,18–29 …”
Section: Introductionmentioning
confidence: 99%